Ecological risk indicators for leached heavy metals from coal ash generated at a malaysian power plant - Abd Manan T.S.B.; Beddu S.; Mohd Kamal N.L.; Mohamad D.; Itam Z.; Khan T.; Machmudah A.; Dutykh D.; Mohtar W.H.M.W.; Jusoh H.; Nazri F.M.; Yapandi M.F.K.M.; et al. (MDPI, 2023)
ash; ecological approach; heavy metal; leaching; power plant; risk assessment; toxicity; Malaysia; Indicator indicator